Vibration Analysis as a Transformative Approach to Condition-Based Monitoring - Tina I. FRANCIS-AKILAKI; Onimi O. ASHAMA; Raymond A. EKEMUBE (FUDMA Journal of Engineering and Technology, 2026)
Effective maintenance of industrial machinery is essential for reducing operational downtime, minimizing maintenance costs, and improving equipment reliability. This study investigates vibration analysis as a diagnostic technique for condition-based monitoring (CBM) of rotating machinery. Experimental investigations were conducted on two industrial systems: a centrifugal pump and a CAT V12 diesel engine. Vibration signals were obtained using tri-axial accelerometers installed at key monitoring points and analyzed using Fast Fourier Transform (FFT) to identify dominant vibration frequencies associated with mechanical faults. The results from the centrifugal pump showed a progressive increase in vibration amplitude with increasing rotational speed, indicating possible shaft misalignment and rotor imbalance. For the diesel engine, vibration characteristics varied with cooling water temperature due to thermal stress and mechanical loading conditions. The measured vibration levels were evaluated using ISO vibration severity standards. The findings demonstrate that vibration analysis is an effective predictive maintenance tool capable of detecting early mechanical faults in industrial machinery. Integrating vibration monitoring into condition-based maintenance programs can significantly enhance equipment reliability, reduce unexpected failures, and improve operational efficiency in industrial systems.
Keywords: Centrifugal pump, Condition-based monitoring, Diesel engine, Fast Fourier Transform, Predictive maintenance, Vibration analysis.